Impact of chronic total occlusion and revascularization strategy in patients with infarct-related cardiogenic shock: a subanalysis of the culprit-shock trial - Braik, Nassim; Guedeney, Paul; Behnes, Michael; Desch, Steffen; Barthélémy, Olivier; Sandri, Marcus; de Waha-Thiele, Suzanne; Fuernau, Georg; Rouanet, Stéphanie; Hauguel-Moreau, Marie; Zeitouni, Michel; Overtchouk, Pavel; et al. (American heart journal, 2021)
Background - The impact of coronary artery chronic total occlusion (CTO) and its management with percutaneous coronary intervention (PCI) in the setting of myocardial infarction (MI) related cardiogenic shock (CS) remains unclear. - Methods - This is a pre-specified analysis from the culprit-lesion-only PCI vs multivessel PCI in CS (CULPRIT-SHOCK) trial which randomized patients presenting with MI and multivessel disease complicated by CS to a culprit-lesion-only or immediate multivessel PCI strategy. CTO was defined by central core-laboratory evaluation. The independent associations between the presence of CTO and adverse outcomes at 30 days and 1 year were assessed using multivariate logistics models. - Results - A noninfarct related CTO was present in 157 of 667 (23.5%) analyzed patients. Patients presenting with CTO had more frequent diabetes mellitus or prior PCI but less frequently presented with ST segment elevation MI as index event. The presence of CTO was associated with higher rate of death at 30 days (adjusted Odds ratio 1.63; 95% confidence interval [CI] 1.01-2.60). Rate of death at 1 year was also increased but did not reach statistical significance (adjusted Odds ratio 1.62; 95%CI 0.99-2.66). Compare to immediate multivessel PCI, a strategy of culprit-lesion-only PCI was associated with lower rates of death or renal replacement therapy at 30 days in patients with and without CTO (Odds ratio 0.79 95%CI 0.42-1.49 and Odds ratio 0.67 95%CI 0.48-0.96, respectively), without significant interaction (P=.68). - Conclusions - In patients with MI-related CS and multivessel disease, the presence of CTO is associated with adverse outcomes while a strategy of culprit-lesion-only PCI seems beneficial regardless of the presence of CTO.
Gesehen am 21.04.2021